2021
DOI: 10.1111/gcb.15553
|View full text |Cite
|
Sign up to set email alerts
|

High microbial diversity stabilizes the responses of soil organic carbon decomposition to warming in the subsoil on the Tibetan Plateau

Abstract: Soil microbes are directly involved in soil organic carbon (SOC) decomposition, yet the importance of microbial biodiversity in regulating the temperature sensitivity of SOC decomposition remains elusive, particularly in alpine regions where climate change is predicted to strongly affect SOC dynamics and ecosystem stability. Here we collected topsoil and subsoil samples along an elevational gradient on the southeastern Tibetan Plateau to explore the temperature sensitivity (Q10) of SOC decomposition in relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(59 citation statements)
references
References 100 publications
7
45
0
Order By: Relevance
“…In a modeling study,Moyano et al (2012) showed that the decomposition of SOC response to moisture depends on soil properties. Thus, these results also partly support the positive biodiversity-ecosystem stability hypothesis(Xu et al 2021).…”
supporting
confidence: 78%
See 2 more Smart Citations
“…In a modeling study,Moyano et al (2012) showed that the decomposition of SOC response to moisture depends on soil properties. Thus, these results also partly support the positive biodiversity-ecosystem stability hypothesis(Xu et al 2021).…”
supporting
confidence: 78%
“…Soil microbial biomass C (MBC), dissolved organic C (DOC), microbial community composition and evolved CO 2 -C were measured throughout the incubation. On the basis of our knowledge, we predicted that (1) greater SOC mineralization would be found with vegetation restoration age; (2) increased soil moisture and temperature would enhance SOC mineralization in all vegetation restoration stages; (3) lower Q 10 would be found with vegetation restoration age, but soil moisture would have a less effect on Q 10 in the SFS than that in the DS, due to soils with longer vegetation restoration years always have a greater biodiversity and might be more adaptive to changes in environmental conditions such as soil moisture (Yang et al 2018;Xu et al 2021).…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, temperature can directly affect relative substrate depolymerization and nutrient acquisition potential, effectively decoupling enzyme relative activities from other regulatory factors, such as nutrient demand and substrate availability. Although microbial trait spaces are not static, as microbiomes adapt to changing conditions, they are likely to constrain both immediate responses and the trajectory of longer-term responses to environmental changes (Bradford, 2013;Conant et al, 2011;Xu et al, 2021). Therefore, it is essential to identify and validate key microbial traits and their environmental constraints in order to build a mechanistic understanding that can be generalized across spatiotemporal scales, and combine theory, measurements and models to improve the representation of microbial processes in Earth system models (Blankinship et al, 2018;Wieder et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, optimal enzyme temperatures are broadly correlated with the optimal growth temperatures of their organisms, as well as with the frequency of specific metabolic pathways, reflecting a concerted evolutionary adaptation to temperature and associated selective pressures (Engqvist, 2018;Somero, 2004). Therefore, variation in substrate and temperature regimes through the soil profile is likely to select for microbiomes producing enzymes with distinct kinetic and thermal properties, which may impose depth-dependent constraints on SOM turnover and responses to warming (Allison and Treseder, 2008;Carrillo et al, 2018;Cavicchioli et al, 2019;Isobe et al, 2019;Nunan et al, 2020;Xu et al, 2021). Microbial community composition and functional potential have indeed been shown to vary strongly with soil depth, reflecting selective adaptation to distinct niches (Blume et al, 2002;Brewer et al, 2019;Diamond et al, 2019;Dove et al, 2021;Eilers et al, 2012;Fierer et al, 2003b;Hansel et al, 2008;Hartmann et al, 2009;Jiao et al, 2018;Liu et al, 2019;Turner et al, 2017;Yan et al, 2019;Zosso et al, 2021).…”
Section: Introductionmentioning
confidence: 99%